KONSEP DIRI PENGGEMAR MUSIK DISKO PEMUDA JAGA EMPAT DESA KANONANG SATU - Vini R. Tigau; Jofie H. Mandang; Theophany D. Kumaat (Program Studi Psikologi Universitas Negeri Manado, 2022)
This study aims to determine the Self-Concept of Disco Music Fans in Jaga 4 Kanonang 1 Village . This is a qualitative descriptive study and used observations, interviews and documentation for data collection,the subject of this research was of teenagers. The results of this study indicate that have a positive self-concept they from the social aspect they remain friendly to the community, if other people criticize it, and it becomes a motivational material. From the psychological aspect, it brings good things for them, when they hear disco music, their mind changes from being stressed to being calm. From the physical aspect, they feel healthier and more enthusiastic, becoming more confident in doing things. they are easier to socialize in the community, even in terms of their religion is still a priority.